Who persistently consumes dietary supplements? A multifaceted analysis using South Korea’s nationally representative health and nutrition examination survey data - Kwon, Hye-Young (Frontiers in Nutrition, 2023)
Objective This study aimed to identify multifaceted factors affecting intake of dietary supplements among Koreans. Methods Korean National Health and Nutrition Examination Survey (KNHANES) data from 2018 to 2020 were obtained, pertaining to functional food intake, health related behaviors and morbidities. A total of 12,031 participants representing the Korean adult population were identified into two groups: 1 year more consumer group (N = 4,345) vs. non-consumer group (N = 7,686). A logistic regression analysis was performed to analyze the predictors of dietary supplement consumptions. Results Sociodemographic variables were associated with dietary supplement use. Participants who were female (odds ratio [OR] = 1.85; 95% CI, 1.59–2.15), older (OR = 1.06; 95% CI, 1.04–1.08), married (OR = 6.39; 95% CI, 3.44–11.85), highly educated, and high income earners consumed significantly more dietary supplements. Non-smoking (OR = 1.27; 95% CI, 1.06–1.53) and performing aerobic exercise (OR = 1.28; 95% CI, 1.13–1.46) predict dietary supplement consumption. Self-rated health status and health-related quality of life increased the likelihood of dietary supplement intake by 1.86 (OR = 1.86; 95% CI, 1.04–3.32) and 7.77 times (OR = 7.77; 95% CI, 1.66–33.40), respectively. The number of chronic diseases, cancer, or stroke was not significantly associated with intake. Those with obesity tended to less consume dietary supplements (OR = 0.85; 95% CI, 0.74–0.97). Hypertension (OR = 3.14; 95% CI, 1.36–7.21), osteoporosis (OR = 1.47; 95% CI, 1.11–1.95), and asthma (OR = 0.44; 95% CI, 0.27–0.73) were significantly associated with the intake. Conclusion Considering that healthy behaviors and subjective health led to the consumption of dietary supplements, whereas current disease or catastrophic experience did not, the intake of dietary supplements should be included in health promotion in Korea.